Innovative aspects of varieties of serve in modern men’s volleyball - Lutkova N.V.; Makarov Yu.M.; Lutkov V.F.; Dakshevich N.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the innovative content of serve efficiency performed by highly qualified volleyball players. Methods and structure of the study. The software of the Italian company Data Project was used: Data Volley 4Pro, through the built-in functionality of which various statistical indicators of competitive activity are analyzed. Indicators of the effectiveness of serve execution were determined in various ways during the Russian Volleyball Championship among men’s teams. 80 games of leading teams with the participation of 96 athletes were analyzed. Results and conclusions. 1. It has been established that at the present stage of development of volleyball, the number of power serves and the efficiency of their implementation is one of the leading characteristics of highly qualified volleyball players. 2. It was revealed that the innovative content of serving by top-class volleyball players is the transition from planning and power to a «hybrid serve». The growth of professional skills of volleyball players is accompanied by the directional dynamics of the use of the specified serve during competitive activity. 3. The concept of «hybrid serve» is formulated, which is defined as an upper straight serve in a jump, the main content of which is the speed of the ball and the degree of its rotation.